THE INFLUENCE OF FINANCIAL LITERACY, FINANCIAL EFFICACY AND FINANCIAL INCLUSION ON INVESTMENT DECISION BEHAVIOR WITH FINANCIAL BEHAVIOR AND FINANCIAL FREEDOM AS AN INTERVENING FOR MEMBERS OF THE EAST FLORES INDONESIAN TEACHERS ASSOCIATION - Agustinus Wilhelmus Uja Werang; Mulyanto Nugroho, Nekky Rahmiyati (CV. Adiba Aisha Amira, 2025)
This study attempts to evaluate the substantive impact of financial literacy, financial efficacy, and financial inclusion on investment decision-making behavior, incorporating financial behavior and financial independence as intervening constructs. Employing a quantitative methodology, the investigation concentrates on a population of 520 members affiliated with IGI. The sample selection employs the Slovin sample technique, yielding a representative sample of 48 individuals. The research outcomes reveal that, in a direct context, financial literacy and financial inclusion fail to exert a statistically significant influence on investment decision-making behavior. On the other hand, financial efficacy emerges as a decisive factor significantly shaping such behavior. Notably, financial behavior is discerned as a mediating factor in the intricate relationship linking financial literacy, financial efficacy, and financial inclusion to investment decision- making behavior. Furthermore, financial freedom assumes the role of a mediator in the indirect association between financial literacy and investment decision- making behavior. However, it is noteworthy that financial freedom does not mediate the connection between financial efficacy and financial inclusion in relation to investment decision-making behavior. These findings contribute to a nuanced understanding of the intricate dynamics influencing financial behavior and investment decision-making, underscoring the pivotal role of financial efficacy and financial behavior as intervening variables. The practical implications of this study offer valuable insights for the development of more effective financial literacy programs and inclusive financial strategies, considering the identified mediating roles